Decision Support System Of Food Selection For Obese Sufferer - Yuana, Yohan Ivandri (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
The purpose of making this application program is to facilitate obese sufferers in choosing appropriate foods to be able to regulate their calorie needs. In this application program the Analytic Hierarchy Process (AHP) method is used to determine the weight of each criterion and alternative. In making application programs using the PHP programming language and MySql database. This application program can display the food chosen by the user based on the level of importance for obesity sufferers, so users can easily determine which foods are good for their health